TYPES OF ILLOCUTIONARY ACT FOUND IN CHARACTER’S CONVERSATION OF THE ADVENTURE OF TINTIN MOVIE: English - Kadek, Wahyu Muliawati; Putu Devi Maharani; Ida Bagus Gde Nova Winarta (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2022)
The writer of this study is interested in classifying the kinds of illocutionary acts found in the movie The Adventures of Tintin. The goal of this research is to determine the types of illocutionary acts shown in the movie The Adventures of Tintin, as well as to analyze the meaning of each illocutionary act in the context of the situation. The information was derived from Peter Jackson's movie The Adventures of Tintin. To characterize the data and answer the study's problems, the researchers employed a descriptive qualitative method. In this study, three theories were employed to analyze the data. First, we'll look at Yule's (1996:48) theory to see how it applies to the type of illocutionary deed depicted in the movie. Second, Leech's (1990:9) theory for analyzing the meaning of a sentence in an utterance and Halliday and Hassan's (1989:2) theory for analyzing the context situation in the movie supports each other. The findings of this research reveal the types of illocutionary acts performed by the character in the movie The Adventures of Tintin, which include representative/assertive, directive, expressive, declarative, and commissive. From the 100 data collected in the movie, the most common act used by the character is expressive illocutionary act, with 26 data or 26%. The least occurrence act used by the character is declaration, which only has 1 or 1% data.